Kepastian Hukum dalam Sistem Praperadilan Pidana terhadap Saksi Pelaku Tindak Pidana Korupsi - Karesya Rezkia Pasha; Akhmad Munawar; Lutfi Yusup Rahmathoni (CV Rewang Rencang, 2024)
Referring to Article 1, Paragraph 2 of Law No. 31 of 2014 of the Republic of Indonesia, “witness-perpetrator” is suspect, defendant, or convict cooperates in supporting the law enforcement process to uncover a criminal act in the same case. The legal issue regarding the construction of pretrial procedures concerning the designation of “witness-perpetrator” in corruption follows: when a witness false testimony, there are provisions in the under Criminal Procedure Code (KUHAP) strictly regulated, emphasizing and essential function of reviewing the legality of the process, based on the initial actions arrest and detention, which are considered coercive measures under the law.